Diabetes distress is more strongly associated with HbA1c than depressive symptoms in adolescents with type 1 diabetes: Results from Diabetes MILES Youth—Australia. Issue 4 (31st January 2018) - Hagger, Virginia; Hendrieckx, Christel; Cameron, Fergus; Pouwer, Frans; Skinner, Timothy C; Speight, Jane
Abstract : Background: Glycated hemoglobin (HbA1c) is higher during adolescence than at any other life stage. Some research among adolescents indicates that depressive symptoms are associated with suboptimal HbA1c. However, research among adults suggests diabetes distress is a stronger predictor of HbA1c than depressive symptoms. Objective: To determine the relative contributions of depressive symptoms and diabetes distress to explain the variance in HbA1c among adolescents with type 1 diabetes. Participants and methods: Diabetes MILES Youth Study respondents aged 13 to 19 years completed questionnaires assessing depressive symptoms (Patient Health Questionnaire for Adolescents: PHQA‐8), diabetes distress (Problem Areas in Diabetes‐Teen version: PAID‐T), and self‐reported socio‐demographic and clinical variables, including their most recent HbA1c. Stepwise hierarchical multiple regression was conducted to examine the contributions of depressive symptoms and diabetes distress to HbA1c. Results: Participants ( N  = 450) had a (mean ± SD) age of 15.7 ± 1.9 years; diabetes duration of 6.9 ± 4.3 years; and 38% ( n  = 169) were male. Twenty‐one percent ( n  = 96) experienced moderate‐to‐severe depressive symptoms (PHQA‐8 ≥ 11) and 36% ( n  = 162) experienced high diabetes distress (PAID‐T > 90). In the final regression model, HbA1c was explained by: diabetes duration ( β  = .14, P  = .001), self‐monitoring of blood glucose ( β  = −.20, P  < .001), and diabetes distress ( β  = .30, P  < .001). Following the addition of diabetes distress, depressive symptoms were no longer significantly associated with HbA1c ( P  = .551). The final model explained 18% of the variance in HbA1c. Conclusions: Consistent with evidence from studies among adults, diabetes distress mediated the relationship between depressive symptoms and HbA1c among adolescents with type 1 diabetes. These findings suggest that clinicians need to be aware of diabetes distress.